Teaching horror literature in a multicultural classroom - Matek, Ljubica (ELOPE (Ljubljana), 2015)
As a genre, horror tends to be marginalized in literature classes because it is often mistakenly perceived to be inappropriate for the classroom environment due to the intensive emotional effects that the genre's typical macabre motifs and topics may produce in the reader. However, this paper argues that, for two reasons, horror texts represent a valid and important addition to a literary syllabus. First, they typically have a positive impact on the students' increased interest in reading, which is, in the pedagogical and scholarly sense, a desirable activity. Second, they tend to contribute significantly to the development of empathy with and tolerance for others, which is an especially valuable learning outcome in a multicultural classroom characterized by implied intercultural communication.
Keywords: empatija; grozljivke (književnost); medkulturnost; strpnost; učni izid; večkulturnost